An UPLC-Q-TOF/MS-Based Analysis of the Differential Composition of Dendrobium officinale in Different Regions. (4th November 2022) - He, Qianqian; Lu, Anjing; Qin, Lin; Zhang, Qianru; Lu, Yanliu; Yang, Zhou; Tan, Daopeng; He, Yuqi
Abstract : Dendrobium officinale ( D. officinale ) is a valuable traditional Chinese herbal medicine with high commercial value. In Chinese Pharmacopoeia (Ch.P., 2020 edition), the quality of D. officinale is mainly evaluated by its polysaccharide content. However, varying growth and production conditions, such as cultivation environment, origin, harvesting process, or processing methods, resulting in highly variable yields, quality, and composition. The aim of this study was to investigate whether the content of secondary metabolites in D. officinale from different origins is consistent with the polysaccharide content. The results showed that the polysaccharide content and pass rate were ranked as GX > AH > GZ > YN. Based on the nontargeted metabolomics approach, we searched for differential components in 22 different regions of D. officinale, including amides, bibenzyls, disaccharide, flavonoids, organic nitrogenous compounds, and phenolic glycosides. The overall expression was opposite to the polysaccharide, and the most expressed was YN, followed by GZ, AH, and GX. These results indicated that the current quality standard for evaluating the quality of D. officinale by polysaccharide content alone is imperfect, and small molecule compounds need to be included as quality markers.